Studies of CdHgTe as a material for x- and γ-ray detectors - Kosyachenko, L.A.; Kulchynsky, V.V.; Maslyanchuk, O.L.; Paranchych, S.Yu.; Sklyarchuk, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Optical, electric and photoelectric properties of Cd₁₋xHgxTe alloy with a low Hg content (x = 0.05) have been studied. The depth of impurity levels determining the conductivity of the material, their concentration and compensation degree, as well as the carrier lifetime and surface-recombination velocity have been found.